METODE DAKWAH MASYARAKAT PESISIR (FENOMENA BUDAYA) - Muh Qadaruddin Abdullah (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
In the maritime community to understand the writer tries to understand, distinguish between religious values and cultural values on the condition of religious and other forms of religious, then the writer can find methods of cultivation of religious values suitable for the maritime community. answer the problem about the condition of religious and religious forms and traditions that deviate from the teachings of Islam and trying to find solutions with preaching methods. This problem is answered by using narrative analysis taken from the Quran and the Hadith and the history of the prophet and the companions. In an attempt to answer these two problems, the authors trace the verses, hadith, history, the talk about books aqidah, morality, worship, and mission and culture. As the end of this writing is expected to give an idea of the value and nature worship, doctrinal camps, so that the character will appear with unclear how exactly it is worship in its relationship as a form of devotion to God Almighty in this case the increase in Aqidah, and repair Akhlaq, to realize a society Khaira Ummah.